Reprodução do capital avícola e campesinato no espaço agrário do agreste paraibano - Correia, Silvana Cristina Costa (2018)
Brazilian poultry farming emerged in the peasant agriculture between the sixteenth and seventeenth centuries, with no mercantile character, destined only for family consumption. The tradition of raising chickens on the farms remains to nowadays, in the 21st century, in the different regions of Brazil. Industrial / capitalist aviculture emerged between the 60s and 70s, with the arrival of the Green Revolution in Brazil through the agriculture modernization. Gradually, it provided spaces for the valorization of capital from the articulation of the state, science and capital. It was both adapted to the parameters of the Green Revolution and adapted to the new pattern of accumulation of globalized monopoly capitalism, made effective after the Brazilian economic opening in the 90s. The use and transformation of territory by globalized capitalism has made unequal forms of valorization and (re) production of poultry capital in the field of different regions of Brazil. Even with the geographic expansion of poultry production in the North, Northeast and Midwest regions, the South and Southeast regions continued in the national ranking as the largest producers and exporters of chicken meat in Brazil. In the case of poultry farming in the Northeast, more precisely, the one developed in the harsh area of the state of Paraíba, it is gradually entering the international market and contributing, in a subordinate and dependent way, to the new pattern of capital accumulation of monopolistic globalized companies The doctoral thesis presented here has the general objective of analyzing the reproduction of poultry capital in the agrarian space of the harsh area of Paraíba and its relationship with the peasantry between 1970 and 2016. For this, in addition to the bibliographic and documentary research and the analysis of secondary data, this study was based on extensive empirical research. From a conceptual point of view, it privileges the concepts of peasantry, space, territory, peasantry resistance, territory of hope, territorialisation of capital and monopolization of the territory by the capital, as well as other concepts of Agrarian Geography, related areas and Marxian theory such as: simple and expanded reproduction of capital, land income, commodities, capital, fictitious capital, financial capital, and others.We find that the agricultural area of the harsh area nowadays is a space for valorization of the capitalist aviculture developed by Guaraves, as it is, contradictorily, a space of resistance represented by the expansion of the alternative poultry for poultry farming developed by the peasants. However, the most different valuable mechanisms of extraction and the land income, in the process of uneven and contradictory development of capitalism in the agrarian space of Paraíba harsh area, they are which determine the amplified reproduction of poultry capital and the simple reproduction of the peasantry.